Interaction between MARK3 (rs11623869), PLCB4 (rs6086746) and GEMIN2 (rs2277458) variants with bone mineral density and serum 25-hidroxivitamin D levels in Mexican Mestizo women - Aparicio-Bautista, Diana I.; Jiménez-Ortega, Rogelio F.; Becerra-Cervera, Adriana; Aquino-Gálvez, Arnoldo; de León-Suárez, Valeria Ponce; Casas-Ávila, Leonora; Salmerón, Jorge; Hidalgo-Bravo, Alberto; Rivera-Paredez, Berenice; Velázquez-Cruz, Rafael (Frontiers in Endocrinology, 2024)
Understanding the genetic factors contributing to variations in bone mineral density (BMD) and vitamin D could provide valuable insights into the pathogenesis of osteoporosis. This study aimed to evaluate the association of single nucleotide variants in MARK3 (rs11623869), PLCB4 (rs6086746), and GEMIN2 (rs2277458) with BMD in Mexican women. Furthermore, we evaluated the gene-gene interaction of these variants in serum 25(OH)D levels and BMD. A genetic risk score (GRS) was created on the basis of the three genetic variants. Genotyping was performed using predesigned TaqMan assays. A significant association was found between the rs6086746-A variant and BMD at the total hip, femoral neck, and lumbar spine, in women aged 45 years or older. However, no association was observed between the variants rs11623869 and rs2277458. The rs11623869 × rs2277458 interaction was associated with total hip (p=0.002) and femoral neck BMD (p=0.013). Similarly, for vitamin D levels, we observed an interaction between the variants rs6086746 × rs2277458 (p=0.021). GRS revealed a significant association with total hip BMD (p trend=0.003) and femoral neck BMD (p trend=0.006), as well as increased vitamin D levels (p trend=0.0003). These findings provide evidence of the individual and joint effect of the MARK3, PLCB4, and GEMIN2 variants on BMD and serum vitamin D levels in Mexican women. This knowledge could help to elucidate the interaction mechanism between BMD-related genetic variants and 25OHD, contributing to the determination of the pathogenesis of osteoporosis and its potential implications during early interventions